Real time visualization of surfactant effects on colloidal self-assembly process - Zhao, Qin. (2009)
The real time video monitoring revealed that the surfactant plays a dominating role to determine the wetting angle of the colloidal suspension in a sessile drop once the suspension was added with surfactant. Meanwhile, surfactant also had great influence on the detailed assembly process and the final lattice structure. Generally, colloidal suspension without surfactant would prefer to form clusters before the particles assemble to the edge. Suspension with anionic surfactant SDS prefer to form close packed HCP structure, while suspension with cationic surfactant DTAB prefer to form amorphous structure. It was also found that, for suspension without addition of surfactant and suspension with nonionic surfactant CO720, square lattice was capable to be formed.